Plan de marketing para la promoción y mejoramiento de los servicios médicos de los Subcentros de Salud del Sistema público de la ciudad de Quevedo, año 2012 - Cantos Franco, Pamela Liceth (2016)
This research was conducted in the city of Quevedo, Los Rios province, taking as reference the Sub-centers in the same city. A duration of approximately 120 days of fieldwork was estimated. The main objective was to determine the incidence of a Marketing Plan in improving the positioning of health services public health system of the city of Quevedo. To conduct the survey due was taken into account population attending these Subcentres, for which a preliminary investigation was conducted in each of the medical units of the parishes, distributed as follows: February 20, Promejoras, San Camilo Viva Alfaro, October 7, totaling 8,200 users who visit monthly. The results of the surveys and some interviews, a SWOT analysis of the services offered Subcentres delimiting the weaknesses they have in customer service and on this basis marketing strategies such as advertising, corporate image and attention was applied to established patient will improve the positioning of the sub health centers. One marketing mix of services specifically to enhance their image users about services Subcentres health of the city of Quevedo by radio campaigns, loudspeakers, conducting applied brochures and posters. At the end of the budget strategies marketing plan health sub-centers together is $ 10,294.90 was established.